Physical attributes and performance differences: Server vs. spiker players in men’s doubles sepak takraw - Gani, Abdul; Resmana, Dadan; Anugrah, Sendy Mohamad (UIR Press, 2024)
Background Problems: Scientific research exploring the comparative analysis of the physical, physiological, and anthropometric characteristics associated with the server and spiker positions in double-category sepak takraw remains relatively scarce. Research Objectives: This study aims to compare the physical, physiological, and anthropometric characteristics between players in the server and spiker positions in the double category of sepak takraw. Methods: The research method used is an observational study with a quantitative approach. This study consisted of 18 male sepak takraw athletes, with 9 athletes each playing as servers and 9 athletes playing as spikers. The statistical analyses were conducted utilizing the SPSS Version 22 application. Findings and Results: The results of this study showed that there were statistically significant differences in body height, aerobic capacity, and leg strength between server and speaker positions (p < 0.05). Meanwhile, there were no significant differences in the variables age, weight, BMI, fat percentage, speed, agility, and flexibility. Dynamic, attractive game requirements and manoeuvres in the air for players in the spiker position have the potential to contribute to superior VO2max values and increased leg muscle strength compared to players in the server position. Conclusion: The conclusion of this study is that athletes in the spiker position show superior anthropometric and physiological attributes compared to those in the server position. Different understandings of the different characteristics associated with each position in the sport of sepak takraw provide new insights and views for coaches and athletes themselves. In addition, it is hoped that this research will have implications for optimizing training programs that adapt to the demands of each position. Furthermore, these findings serve as a reference for talent search events that assist in the identification and development of athletes with optimal physiological profiles for their respective roles in double-category sepak takraw.